AN ANALYSIS OF CODE-SWITCHING IN INDONESIAN TELEVISION ADVERTISEMENTS - Farrima, Stevani; Dahnilsyah, Dahnilsyah; Safriyanti, Maria (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research investigates the types of code-switching between Indonesian and English and vice versa in Indonesian television advertisements. The limitation of this research was on the use of code switching cosmetic product which occurred in Indonesian Television advertisements. The technique used to collect the data was Documentary technique means reading, studying, and analyzing all the data. This research was conducted by using content analysis methodology, with the code-switching being identified, noted, analyzed and finally categorized into the framework developed by Hoffman who proposed the types of code-switching: intra-sentential switching, inter-sentential switching and tag switching. A data of 30 cosmetic advertisements are used in analyzing code-switching. The advertisements are gotten from some kinds of cosmetic brands, such as Emina, Fair and Lovely, Fit Me, Garnier, Emina, Lakme 9to5, Loreal Paris, Marina, Maybelline Poise, Pons, Purbasari, Vaseline, and Wardah. The result showed that the most frequently used code-switching form in Indonesian television advertisements was intra-sentential switching (83,33%), followed by inter-sentential switching (11,11%), and tag switching (5,56%).Key Words: Code-Switching, Types, Sociolinguistic.